Persepsi Masyarakat Mengenai Kinerja Pelayanan PAMSIMAS di Kota Semarang - Trenggono, Fransisca Chrystalia; Wahyono, Hadi (Magister Pembangunan Wilayah dan Kota,Undip, 2017)
In 2016, ASPAMS as forum association of BPSPAMS had monitored and evaluated performance of BPSPAMS in sub-districts having received Pamsimas. Result of monitoring and evaluation is a list of BPSPAMS in sub-districts with the best performance until the worst performance. This study aims to deeply analyze how the service performance of Pamsimas in sub-districts with independent, evolve, grow, and cease predicate using descriptive qualitative method. Data collecting technique used interview, observation, and document review. Results of study show that Pamsimas service performance in Mijen Sub-district is good, Pamsimas service performance in Cepoko and Mangunharjo Sub-district is poor, while Pamsimas was unsuccessful in Sadeng Sub-district. The service performance of Pamsimas in Mijen, Cepoko, Mangunharjo, and Sadeng Sub-districts is affected by water resource, construction work that not according to the design plan, topography, quality standard of water storage, management commitment and integrity, and customers ability and willingness to pay.